Self-focusing dynamics of Lorentz-Gaussian beams in Kerr media - Zheng, Hong Ping; Chen, Rui Pin; Ooi, Chong Heng Raymond (Old City Publishing, 2013)
The nonlinear dynamical property of Lorentz-Gaussian beams in Kerr media is investigated analytically and numerically by using the nonlinear Schrödinger (NLS) equation. The evolution of a Lorentz-Gaussian beam width in the root-mean-square (RMS) sense is analytically obtained. The beam propagation factors and the critical powers of the Lorentz-Gaussian beams are demonstrated. Numerical simulations described in more detail for the nonlinear dynamics of Lorentz-Gaussian beams in the Kerr media. © 2013 Old City Publishing, Inc.